Le développement des espoirs et des peurs envers l’avenir dans le domaine scolaire chez les élèves de cycle 3 - Gaëlle Lefe; Philippe Guimard; Agnès Florin (Recherches en Éducation)
The hopes and fears of children can be conceptualized as “hopes-for selves” and on “fears selves”, both as subsets of the “possible selves” (PS) concept. The PS is defined as an individual's cognitive representations of the self in the future. The aim of this longitudinal study is to examine children's development of the possible selves, and mainly the academic PS, which has not been studied to date. A first version of the self-report Possible Selves Questionnaire has been developed and has been administered to 124 students. Participants were followed during a three year period (from 8 to 10 years old). Results shows the academic possible selves increase with age, where this also is the case for the "hopes-for selves" and "fears selves". In conclusion, the development of children's academic possible selves’ is discussed, and particularly while in an academic transition.